INTERNATIONAL MARKETING AS A REFLECTION OF CONTEMPORARY GLOBALIZATION PROCESSES - Hrechanyk, N.Yu. (The actual problems of regional economy development, 2018)
The modern world economic space represents a global system of economic interconnections and interdependencies that covers all local and national economic systems that are linked to each other by the international division of labor and various forms of integration at the level of resources, productive forces and political and legal relations. Globalization leads to the participation of both individual companies and society as a whole in global competition: markets, organizations, languages, and cultures no longer have clear territorial boundaries, borders, barriers. Globalization makes available all world resources: natural, technological, informational, intellectual. This significantly accelerates development and increases the opportunities for companies in any market and organization. International marketing - a set of activities of the company for the implementation of foreign economic activities outside of their country in order to achieve new commercial goals. International marketing acts as an appropriate reaction of the business world to such processes as: expansion of partnerships in the world market, growth of production opportunities, rapid updating of the product range, frequent changes in the nature and structure of market demand, its market fluctuations, the common and distinctive features of individual cultures informational security and so on.